Principles of fair market valuation of rights under leasing agreement with the option to purchase the property - Shchepot’ev , A.V. (International Journal of Psychosocial Rehabilitation, 2020)
The objectives of the study are aimed at improving of the tools for identifying and evaluating hidden assets of a company expressed in legal rights under leasing agreements with the property purchase option. Such rights can be identified as an asset, valued and will bring economic benefits to an economic entity. The methods of analysis, generalization, synthesis and comparison were used in the research.The article shows the basic principles of eligibility evaluation under the leasing agreement, explains their economic essence, describes the theoretical mechanism for the redistribution of assets between affiliates through the transfer of rights and obligations under leasing agreements.